Communication Supports and Best Practices: Ensuring People With Aphasia Have an Effective Means of Expressing Needs and Wishes. Issue 4 (October 2017) - King, Julia M.; Simmons-Mackie, Nina
Abstract : When people with aphasia have difficulty communicating, there is a risk for miscommunication and negative outcomes related to medical care and safety (Blackstone, Beukelman, & Yorkston, 2015 ). This risk can be reduced by ensuring that each person with aphasia can communicate effectively when using different types of discourse and at different points in the rehabilitation process. People with aphasia may need communication supports, which could entail use of any intervention program, technique, strategy, training, or modification that supplements their receptive and expressive language skills to increase communicative effectiveness. Effective communication is addressed in best practice recommendations and guidelines for aphasia as well as The Joint Commission Standards for Patient-Centered Communication (Aphasia United, 2014 ;NHMRC AARP, 2014 ;N. Simmons-Mackie et al., 2017 ;The Joint Commission, 2010 ). This article summarizes how incorporating communication supports into varied forms of discourse and all aspects of aphasia rehabilitation and care aligns with best clinical practices and national accreditation requirements.